A organização das práticas de alfabetização na escola particular a partir da inserção das crianças de seis anos no ensino fundamental - Maria do Carmo Gallo Cruz (2013)
The research that is a result of this essay had as the principal aim the realization of the analysis of some proposals in the instruction of reading and writing of some private schools in Belo Horizonte city, considering the knowledge and skills related in the acquisition of writing language in these schools which are significant to children about six years old to go in to the fundamental learning. The study was motivated by the change in the basic education organization by the Federal Law nº 11.274/06 that enlarged the length of fundamental learning to nine years. We decided to perform a study in a contracting way, as we considered different ways of admission of six year-old children in the fundamental learning: they could have studied in a children education course or not and they could have come from the own learning institution. The data assessment enveloped teachers and coordinators of the first grade from three schools in Belo Horizonte city known as their high level in academic terms. To achieve the research aims, it was adopted a qualitative approach with a semi-structured interview and a documented analysis as the data assessment. The data analysis was supported in a joint of authors who investigate the conceptions of reading and writing and letters and the study about efficient schools. We deepened some questions related with pedagogic ministration, a curriculum proposal; especially the Literacy matter and the evaluated strategies occurred in the first grade of fundamental course. The results revealed that there is a relationship between the evaluating procedures used in the insertion process of children in schools and the directives which define the pedagogic planning of reading and writing practices in this new education scenery.